An Enforcement-Coalition Model: Fishermen and Authorities forming Coalitions - Lone Grønbæk Kronbak; Marko Lindroos (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
The paper sets up a four-stage enforcement model of fish quotas. The purpose of the paper is to show how the level of enforcement set by the authorities af-fects the way fishermen form coalitions. We show that a high level of control effort yields less cooperation among fishermen, while in the case of low control effort, coalitions are somewhat self-enforcing. The paper further discusses how the optimal enforcement level changes when the coalition formation among au-thorities changes: centralised, partly centralised and decentralised authorities. We show that decentralised authorities set a lower level of control effort com-pared to the centralised authorities. The theoretical results are illustrated by simulations of the Baltic Sea cod fishery.
Keywords: C70; Q22; Q28; 330; Coalition formation; Fisheries management; Quota enforcement; Self-enforcing policy; Seefischerei; Kooperatives Spiel; Koalition; Fischereiressourcen; Theorie; Ostsee